2017
DOI: 10.37358/rc.17.10.5904
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Biochemical Variables and the Quality of Life in Patients with Chronic Heart Failure

Abstract: The aims of this paper were to asses the quality of life with the use of the SF36 Questionnaire in patients with chronic heart failure and to establish the relationship between specific biochemical variables and the various aspects of the quality of life. The scores for various components of the quality of life were significantly affected by hemoglobin levels, creatinine clearance, fibrinogen levels and gamma-glutamyl-transferase levels, while lipid fractions and liver enzymes did not proove to have a signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Subsequently it was observed that serum CgA increases in patients with pheos/EAPs, as well as in other hormone secreting or non-hormone secreting neuroendocrine tumors such as gastroenteropancreatic tumors, medullary thyroid carcinoma, pituitary tumors (except of prolactinomas), neuroblastomas (Plesoianu et al 2017). The largest amounts of CgA are within the neuroendocrine cells of the adrenal medulla and in the storage granules of the sympathetic nerves (Mirica et al 2018).…”
Section: Biochemical Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently it was observed that serum CgA increases in patients with pheos/EAPs, as well as in other hormone secreting or non-hormone secreting neuroendocrine tumors such as gastroenteropancreatic tumors, medullary thyroid carcinoma, pituitary tumors (except of prolactinomas), neuroblastomas (Plesoianu et al 2017). The largest amounts of CgA are within the neuroendocrine cells of the adrenal medulla and in the storage granules of the sympathetic nerves (Mirica et al 2018).…”
Section: Biochemical Testsmentioning
confidence: 99%
“…The largest amounts of CgA are within the neuroendocrine cells of the adrenal medulla and in the storage granules of the sympathetic nerves (Mirica et al 2018). Proton pump inhibitors can raise the levels of CgA to 2-3 times (Gut et al 2016) other conditions that can raise the CgA levels are hepatic and cardiac insufficiency, kidney dysfunction, rheumatoid arthritis, inflammatory bowel disease, and atrophic gastritis (Plesoianu et al 2017).…”
Section: Biochemical Testsmentioning
confidence: 99%
“…Nearly half (49.6%) of the patients with chronic heart failure included in our study, hospitalized for cardiac failure decompensation had at least moderate renal impairment, evaluated by GFR<60mL/min/1.73m 2 . It is thus confirmed that renal dysfunction has a high prevalence in patients with severe heart failure, data from the literature suggesting an estimated prevalence of renal dysfunction in patients with heart failure between 30% and 54% and increase cardiovascular risk and reduces the quality of life [14][15][16][17][18][19][20][21]. Conversely, cardiac disease is a very common comorbidity not only in patients with COPD [22] but also in cases with chronic kidney disease (CKD).…”
Section: Resultsmentioning
confidence: 93%
“…The physico-chemical theory of inflammation also has an important shortcoming in that it attempts to reduce the inflammatory process to the laws of physical chemistry and colloidal chemistry [34][35][36]. Such an approach to the problem ignores the biological essence of the inflammatory reaction, and therefore has a mechanistic character [37]. From the point of view of physicochemical theory, inflammation remains an exclusively local process, overcoming the role of regulator y systems and mechanisms in the occurrence of the inflammation process, and especially the importance of the nervous system.…”
Section: Developing Physical Chemistry and Biological Chemistry In Thmentioning
confidence: 99%